Study on the early warning of cracking and water inrush risk of coal mine roof and floor - Zhang, Shichao; Wei, Xiuqi; Tang, Liming; Duan, Wenshuo; Gong, Bin; Mu, Chaomin; Zhang, Shujin (Frontiers in Earth Science, 2024)
Microseismic monitoring has proven to be an effective approach for detecting and preempting water inrush incidents within mining operations. However, challenges persist, particularly in terms of relying on a singular early warning index and the complexities involved in quantification. In response to these obstacles, a dedicated investigation was undertaken against the backdrop of mining activities at the 11023 working face of Paner Coal Mine.Primarily, a novel methodology for categorizing the roof and floor into distinct zones was established based on the vertical distribution of microseismic events. Furthermore, this study delves into the dynamic evolution of key source parameters, such as microseismic energy, apparent stress, and apparent volume, amidst mining disturbances, enabling a comprehensive evaluation of the risk associated with roof and floor cracking, as well as potential water inrush incidents. A groundbreaking approach to early warning was proposed, operating on three pivotal dimensions: the depth of fractures, the intensity of fractures, and the likelihood of water inrush. Through rigorous validation during mining operations at the 11023 working face, the efficacy was substantiated. Ultimately, the achievements offer invaluable insights and practical guidance for the advancement and implementation of water inrush early warning systems in coal mining contexts.